2012 Proceedings IEEE INFOCOM Workshops 2012
DOI: 10.1109/infcomw.2012.6193491
|View full text |Cite
|
Sign up to set email alerts
|

Content retrieval using cloud-based DNS

Abstract: Abstract-Cloud-computing systems are rapidly gaining momentum, providing flexible alternatives to many services. We study the Domain Name System (DNS) service, used to convert host names to IP addresses, which has historically been provided by a client's Internet Service Provider (ISP). With the advent of cloud-based DNS providers such as Google and OpenDNS, clients are increasingly using these DNS systems for URL and other name resolution.Performance degradation with cloud-based DNS has been reported, especia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Several studies have shown the potential advantages of a "personalized" selection of DNS servers based on responsiveness [1,3,4]. The close relationship between many web applications and DNS demands a careful analysis of Copyright is held by the author/owner(s).…”
Section: Motivationmentioning
confidence: 99%
“…Several studies have shown the potential advantages of a "personalized" selection of DNS servers based on responsiveness [1,3,4]. The close relationship between many web applications and DNS demands a careful analysis of Copyright is held by the author/owner(s).…”
Section: Motivationmentioning
confidence: 99%
“…For accurate measurements, end hosts at strategic locations are used (Francis, et al, 2001), latency is estimated based on coordinated using landmark hosts (Ng & Zhang, 2001) or DNS queries (Gummadi, Saroiu, & S., 2002), or routing topology (Dabek, Cox, Kaashoek, & Morris, 2004) (H. Madhyastha, 2006). Measured latencies also help select target servers to achieve specified optimization goals in routing, content distribution networks, and cloud computing (Wendell, Jiang, Freedman, & Rexford, 2010) (Khosla, Fahmy, & Hu, 2012) (Ding, Chen, T., & Fu, 2010). Their objective function is to minimize the total execution time and select best replica servers considering server loads, cost and locations.…”
Section: Introductionmentioning
confidence: 99%